Median-of-means approach for repeated measures data. Issue 17 (9th August 2021) - Zhang, Yangchun; Liu, Pengfei
Abstract: In this paper, we introduce the median-of-means approach for estimating unknown parameters in multiple linear regression model and the regression model with autocorrelated error. The proposed estimators are not only robust against the outliers of data but also proved to be consistent. Extensive numerical simulations and one real dataset are presented to show the performances of new estimators.